High glucose rapidly activates the nitric oxide/cyclic nucleotide pathway in human platelets via an osmotic mechanism - Massucco, Paola; Mattiello, Luigi; Russo, Isabella; Traversa, Monica; Doronzo, Gabriella; Anfossi, Giovanni; Trovati, Mariella (Thrombosis and Haemostasis, 2005)
The aim was to evaluate whether high glucose influences the nitric oxide (NO)/cyclic nucleotide pathway in human platelets via osmotic stress and to clarify the role of protein kinase C (PKC) in this phenomenon. The study was carried out on 33 healthy lean male volunteers, aged 28.3±1.3 years. NO synthesis was detected as L-citrulline production after L-arginine incubation in platelets incubated for 6 min with 22.0 mM D-glucose and isoosmolar concentrations of mannitol, L-glucose and fructose. To evaluate the influence of PKC, experiments with D-glucose and mannitol were repeated in the presence of the PKC-beta selective inhibitor LY379196, and NO synthesis was detected after a 6-min incubation with phorbol 12-mirystate 13-acetate (PMA), a non-selective PKC activator. Platelet content of guano-sine-3’, 5’-cyclic monophosphate (cGMP) and adenosine-3’, 5’-cyclic monophosphate (cAMP) was measured by radio-immunoassay in platelets incubated with iso-osmolar concentrations of D-glucose, mannitol, L-glucose and fructose. NO-dependence of cyclic nucleotide enhancements was evaluated by inhibiting NO synthase and guanylate cyclase. Platelet aggregation to ADP and collagen was evaluated in Platelet-Rich Plasma (PRP) in the presence of a 6-min incubation with D-glucose and mannitol, both without and with LY379196 and the guany-late cyclase inhibitor (H-[1, 2, 4]Oxadiazolo [4, 3-a]quinoxaline-1-one)(ODQ). Iso-osmolar concentrations of D-glucose, mannitol, L-glucose and fructose, and PMA increased NO production (p=0.0001). Effects of D-glucose and mannitol were blunted by LY379196. D-glucose and mannitol enhanced platelet cGMP and cAMP (p=0.0001) with a mechanism blunted by NO synthase and guanylate-cyclase inhibition, but did not modify platelet aggregation. In conclusion, glucose activates the NO/cyclic nucleotide pathway in human platelets with an osmotic mechanism mediated by PKC-beta.
Keywords: Glucose; platelets; nitric oxide; osmotic stress; protein kinase C